Chile - boosting productivity growth by strengthening competition, entrepreneurship and innovation - Schwellnus, Cyrille (OECD Economics Department working papers, 2010)
Productivity growth has declined since the late 1990s, slowing the catching-up process. Structural reforms to strengthen competition, entrepreneurship and innovation would go a long way toward enhancing it. Recent competition policy reforms that strengthen enforcement of cartel law must now be implemented effectively. The National Economic Prosecutor should receive sufficient resources and the ceiling on fines against cartels, which has recently been raised, may need to be reviewed again. Entrepreneurship should be strengthened by reducing regulatory "red tape" for start-ups and simplifying bankruptcy procedures. Recent reforms to the innovation policy framework are welcome but the focus on sectoral priority clusters will need to be accompanied by appropriate monitoring procedures and sunset clauses for public support. This Working Paper relates to the 2010 Economic Survey of Chile (www.oecd.org/eco/surveys/Chile)